Feeding ecology and activity patterns of Hippopotamus amphibious in the Dhidhessa Wildlife Sanctuary, Southwestern Ethiopia - Girma Gizachew Tefera; Tadesse Habtamu Tessema; Tibebu Alemu Bekere; Tariku Mekonnen Gutema (PLoS ONE, 2025)
Understanding the dietary composition and activity patterns of hippopotamuses (Hippopotamus amphibious) is critical for assessing their ecological role within their habitat. This study investigated the feeding habits and behavioral rhythms of common hippopotamuses in the Dhidhessa Wildlife Sanctuary (DWS), Ethiopia, from 2022 to 2023. Dietary data were collected through direct observation of fresh feeding signs and fecal analysis, while activity patterns were recorded via continuous focal sampling of adult males and females at 30-minute intervals. Hippopotamuses allocated 30.1% of their time to resting, followed by movement (23.7%). Vocalizations (barking) constituted 53.1% of recorded behaviors, while yawning accounted for 46.9%. Males exhibited significantly more resting behavior than females. Peak feeding and movement occurred during early morning and late afternoon, whereas resting peaked at midday. Both sexes displayed higher frequencies of barking and yawning in the afternoon. Dietary analysis identified 34 plant species from 12 families consumed by hippos. Poaceae dominated their diet (60%), while Combretaceae contributed the least (0.5%). Typha latifolia was the most frequently consumed species (9.4%), followed by Eriochloa fatmensis (8.7%). Seasonal variation was evident, with 76.7% of foraging occurring in the wet season compared to 23.3% in the dry season. Twenty-one forage species were available year-round. These findings highlight the importance of seasonal resource availability and temporal activity shifts in hippopotamus ecology. Conservation strategies in DWS should prioritize habitat management to ensure sustainable ecosystem functionality.